Nanoliposomal Encapsulation and Purification of AngiotensinConverting Enzyme Inhibitor Peptides from Ulva rigida - Şensu, Eda; Koku, Harun; Demircan, Evren; Şişman, Sebahat; Gülseren, İbrahim; Karaduman, Tuğçe; Çakır, Bilal; Okudan, Emine Şükran; Duruksu, Gökhan; Özçelik, Beraat; Yücetepe, Aysun; Çakır, Bilal; et al. (American Chemical Society, 2025)
ABSTRACT: Angiotensin-converting enzyme inhibitory peptides derived from natural sources may be effective in the treatment of hypertension without causing side effects compared with existing angiotensin-converting enzyme (ACE) inhibitors. Naturally derived antihypertensive peptides are therefore considered a promising alternative for the prevention or treatment of hypertension. Therefore, the study aimed to purify and identify ACEinhibitory peptides from the green macroalgae Ulva rigida. In addition, the encapsulation of the purified peptides showed the highest ACE-inhibitory activity by chitosan-coated nanoliposomes, and the characterization of nanoliposomes was evaluated. Protein hydrolysates were obtained from U. rigida through enzymatic hydrolysis. The hydrolysates were separated into molecular weights of <3, <5, and <10 kDa through ultrafiltration membrane separation (UFMS). The <3 kDa fraction (UFMS-3) that exhibited the highest ACE-inhibitory activity (77.02%, 1 mg/mL) was purified using ion-exchange chromatography. Fraction-1 (IEC-F1) obtained from the ion-exchange purification showed an impressive 82.03% ACE-inhibitory activity. Moreover, peptide sequences of IEC-F1 were identified by LC-MS/MS, and their bioactive properties were determined in silico. After that, IEC-F1, with a strong ACEinhibitory activity, was loaded into chitosan-coated nanoliposomes to improve their stability for encapsulation. Physical stability (ζ- potential, polydispersity index, particle size), thermal (DSC) and morphological properties (SEM), and FT-IR analyses were carried out for the characterization of nanoliposomes. Encapsulation efficiency was found to be 92.0 ± 4.5%. After encapsulation, the ACEinhibitory activity of IEC-F1 was protected by 37.5%. Overall, the obtained findings indicate that the hydrolysate produced by the successive hydrolysis of U. rigida macroalgae with pepsin and trypsin contains peptides with strong ACE-inhibitory action. Furthermore, the chitosan-coated nanoliposome method was determined to be an effective carrier for the delivery of peptide fractions, showing ACE-inhibitory activity. The formulation of chitosan-coated nanoliposomes for peptide fractions from U. rigidarepresents an innovative approach that allows the development of functional and stable products.
Keywords: Biopolymers; Encapsulation; Hydrolysis; Particle size; Peptides and proteins